Utopian Montage: exploring transnational folk cinemas online as part of the 2020 Folk Film Gathering film festival during the Covid-19 pandemic. Issue 1 (30th November 2021) - Chambers, Jamie; Higbee, Will
Abstract : This essay explores some of the simultaneous limitations and affordances the Covid-19 pandemic has created for emergent perspectives upon a transnational folk cinema. Merging aspects of more traditional scholarly enquiry with the research-by-practice embodied within Scotland's Folk Film Gathering film festival, we position two case studies – of Nadir Bouhmouch's Amussu (2020 ) and the Amber Collective's Like Father (2001 ) respectively – within some of the broader question underlying attempts to bring the conviviality of community-focussed filmmaking and cinema-going online during the pandemic.